The rise of middle classes in Southeast Asia - Shiraishi, Takashi; Pasuk Phongpaichit (Kyoto area studies on Asia, 2008)
The rise of the new middle classes in Southeast Asia brought about important transformations in various countries politically, socially, economically and culturally, while producing new East Asian lifestyles that transcend national boundaries and causing the reorganization of urban space.